Leptin Levels in Slow Coronary Flow - Yilmaz, Mucahid; Yavuzkir, Mustafa Ferzeyn; Dagli, Necati; Korkmaz, Hasan; Kurtoglu, Ertugrul; Bilen, Mehmet Nail; Akbulut, Mehmet (Drunpp-Sarajevo, 2012)
Objective: It has been accepted that slow coronary flow (SCF) is a variant of coronary artery diesease (CAD). It is not known that leptin plays an important role in the etiopathogenesis of CAD. We aimed to evaluate whether there was a significant difference in serum leptin levels between patients with normal coronary flow and those with SCF. Method: The study population consisted of a total of 80 subjects, 40 patients with SCF and 40 healty subjects with normal coronary arteries (NCA). Serum leptin levels were determined by a radioimmunoassay technique. Results: Age, Gender, hypertension, diabetes mellitus (DM), body mass index (BMI), systolic blood pressure, and levels of total cholesterol, creatinine, C-reactive protein and other biochemical parameters were not different between SCF group and NCA group, as were serum leptin levels (32.6 +/- 40.9 versus 44.2 +/- 43.8, p>0.05). When SCF and NCA groups were divided into two groups according to the presence or absence of DM, leptin levels were again did not differ between those with DM in SCF and those with DM in NCA, as were between those without DM in SCF group and those without DM in NCA group (p>0.05). It was found that leptin levels correlated with BMI, height and levels of serum CRP, LDL-cholesterol, trigliseride, white blood cells and platelets (p< 0.05). Conclusion: We did not find any statistically significant differences in leptin levels between SCF and NCA groups. Correlation of leptin levels with LDL-C, trigliseride, CRP and BMI may suggest that leptin may play an important role in the atherosclerotic process.
Keywords: leptin; slow coronary flow; normal coronary flow